Atomic scale mechanism of clay minerals dissolution revealed by ab initio simulations. (15th January 2021) - Schliemann, René; Churakov, Sergey V.
Abstract: Large-scale ab initio Meta-Dynamics simulations were applied to elucidate the molecular mechanism and reaction free energies of pyrophyllite dissolution at the (1 1 0) edge surface in pure water at close to neutral pH under far from equilibrium conditions. The simulation setup allows realistic representation of the clay mineral surface and explicit consideration of solvent dynamics at finite temperature. The simulation reveals that dissolution of a single tetrahedral or an octahedral unit from the clay mineral edge is a complex multi-step process with several reaction intermediates. Typically, each reaction step changes denticity of the reacting site in a step-by-step manner and leads, eventually, to the leaching of ions forming octahedral and tetrahedral sheets of the phyllosilicate. The solvent rearrangement and the proton transfer reactions in the first and the second coordination shell of the dissolving unit play a critical role in the stabilization of reaction intermediates and the net progress of the dissolution reactions. The overall reaction mechanism can be rationalized as sequence of concurrent and reversible elementary reaction events, which are: (1) the nucleophilic attack of H2 O molecules or OH groups on the dissolving surface site. (2) ligand exchange reactions in the first coordination shell of the reacting sites leading to changes of its conformation and denticity at the mineral surface. (3) collective proton transfer reactions between the acidic and basic oxygen sites mediated via a chain of the hydrogen bonded molecules in the first and second coordination shell of the reacting site. The results obtained in this study are general and applicable to the group of 2:1 phyllosilicates in a wide range of chemical and thermodynamic conditions.